Mediasi Kepuasan Pengunjung pada Pengaruh Kualitas Pelayanan Dan Penetapan Harga terhadap Loyalitas Pengunjung Objek Wisata Air Tejun Bah Biak Kabupaten Simalungun - Liharman Saragih; Taufik Parinduri; Damayanti Safitri (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Small and medium-sized businesses (MSMEs) are crucial to a nation's economy, which has lately emerged as one of the primary forces behind the development of the public monetary system. The state of the economy is getting worse right now. SMEs with the financial means use tactics, of course. The goal of this study is to determine whether to evaluate the method that SMEs using chicken and fish (Bakar Goreng) employ to increase the volume of their goods. An illuminating strategy with a subjective methodology, together with interview and inspection techniques, is the exploration strategy employed. The study's unintended consequences are. The advertising strategy utilized in BaReng to increase the seriousness of MSME items is to divide the market into showcases without considering consumer behavior, without any special guidelines, and without restricting customer time. Choosing to display the time before significant events like Christmas or Eid. Use a variety of advertising strategies to raise awareness of product quality and price. Face the competition by providing products with enticing bundling and affordable prices. The availability of raw materials and exceptional product quality are supportive factors for the MSME promotion system in raising the seriousness of MSME products. The narrow market network, the lack of online media activities used as a tool for promotion, and the intense rivalry are the repressive factors for MSMEs in presenting procedures in increasing the intensity of MSME products.